Understanding why complex projects overrun: developing a framework for identifying and managing risks - Alexander, James (Curtin University, 2015)
Despite a growing wealth of experience and knowledge concerning projects they experience cost overruns. Answering a call from leading academics for new research perspectives on projects, this thesis examines project cost overruns using a systemic modelling perspective and a case study design. The findings suggest that feedback dynamics involving loss of client trust; delay triggers such as design changes; and contextual conditions such as human resource policies, form a complex system that can induce overruns.